(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
Mangrove ecosystem is a specific ecosystem that only take about 2% of total land in the earth. Indonesian mangrove ecosystem is the widest in the world and as a center of distributioan and ecosystem biodiversity, however it undergoes rapid and dramatic destruction. In just 11 years, between 1982-1993, more than 50% of Indonesian mangrove disappeared. The most factor threatening the mangrove ecosystem is human activities, including convertion to aquaculture, deforestation, and environmental pollution. Other factors such as reclamation, sedimentation, and natural disturbance are also contributed to the disappearance of the mangrove. Mangrove ecosystem is very important in term of socio-economic and ecology functions. Because of its functions, wide range of people alaways paid attention whenever mangrove restoration taken place. Mangrove restoration potentially increases mangrove resource value, protect the coastal area from destruction, conserve biodiversity, fish production and both of directly and indirectly support the life of surrounding people. Â© 2003 Jurusan Biologi FMIPA UNS Surakarta Key words: mangrove, restoration, management, Java.